Carbon-encapsulated niobium carbonitride with high volumetric capacitance and wide potential windows in aqueous pseudocapacitors. (1st December 2019) - Yan, Hao; Chen, Sheng; Zhang, Daoming; Wang, Zhiqiang; Ma, Jingyuan; Wen, Wen; Wang, Yakun; Wang, Hui-Qiong; Dai, Yang; Zheng, Jin-Cheng; Wu, Lijun; Zhu, Yimei
Abstract: Electrochemical capacitors deliver high power and have long operational lives; however, their energy densities are limited. Compared to carbon-based electrical double-layer capacitors, pseudocapacitors with an aqueous electrolyte are predicated to provide both high gravimetric and volumetric capacitance while being cost-effective and eco-friendly. However, their narrow operational potential windows limit the practical delivery of energy. In this study, we synthesized novel NbCx N1-x nanoparticles encapsulated in a uniform carbon layer. This pseudocapacitive material exhibits a high volumetric capacitance, a wide potential window stability (∼345 F cm −3, 2.1 V, in 1 M of Li2 SO4 ), and a long cycling life (>10 000 cycles). Moreover, the symmetric cells (2.2 V, in 1 M of Li2 SO4 ) exhibit high energy density as well as excellent cyclability and rate performances. These findings provide new opportunities for the design of aqueous energy storage devices having a wide applied potential difference and excellent performance. Graphical abstract: High performance carbon-encapsulated NbCx N1-x materials with high volumetric pseudocapacitance and wide potential window stability (2.2 V symmetric cell, 37 Wh L −1, > 10 4 cycles).Image 1 Highlights: Carbon-encapsulated niobium carbonitride is synthesized by one step. As the electrode active material for high performance supercapacitor. An electrode potential of 2.1 V and 345 F cm −3 can be obtained in 1 M Li2 SO4 . Symmetric cell with 1 M Li2 SO4 can be operated with a potential difference of 2.2 V Symmetric cell with 1 M Li2 SO4 electrolyte delivers 37 W h L −1 .